Multiphase structural models and hyperpolarizability calculations explain second-order nonlinear optical properties of stilbazolium ions - Ashcroft, Christopher M.; Cole, Jacqueline M.; Lin, Tze Chia; Lee, Seung Chul; Malaspina, Lorraine A.; Kwon, O. Pil (Physical Review Materials, 2020)
The stilbazolium-based organic salt, DAST, is probably the most well-known commercial organic non-linear optical (NLO) material. Chemical derivatives of DAST have therefore been designed to engender even better performing NLO materials; the DAST-derivative, BP3, is one success in this regard. This paper provides a proof-of-principle in the use of structure factors, F, to determine the effects of the crystalline environment on intramolecular charge transfer (ICT), and thus the second-order NLO response of such molecules. A concerted experimental and computational approach is adopted. In particular, the application of the relatively new x-ray wave function refinement method, which tempers theoretical calculations with experimentally derived structure factors to yield an isolated molecule influenced by crystal-field forces, enables the impact of those crystal-field forces on ICT to be established. This study employs high-resolution x-ray diffraction data for its experimental component, this resolution being necessary given the marked challenges that are associated with the complicated interionic interactions within an organic salt. The results presented pinpoint the molecular-scale features that afford BP3 better second-order NLO prospects than DAST, laying the foundations for the molecular engineering of DAST derivatives that are better tailored to optimize NLO function.
Keywords: Computational approach; High-resolution X-ray diffraction data; Interionic interactions; Intramolecular charge transfers; Molecular engineering; Non-linear optical material; Second-order nonlinear optical property; Theoretical calculations